Board Game as An Evaluation Instrument for Classification of Living Things Material - Kaka, Trifonia Yulianti Bebe; Istikomayanti, Yuswa; Aldya, Riantina Fitra (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
The aim of the research was to develop a board game on the classification of living things that were suitable for use by class VII students at MTs Muhammadiyah 1 Malang. This research used the ADDIE method, which consists of 5 stages: analysis design, development, implementation, and evaluation. The time and place of this research were carried out in class VII at MTs Muhammadiyah 1 Malang. This research was conducted from August to September 2023. Validation by media experts to assess the board game being developed, namely in terms of image, colour and writing aspects. Results of a large-scale student response questionnaire from 24 VII grade students. Experts rated the results of the research; the evaluation instrument obtained used an average of 66% (valid), the assessors from media experts obtained a score of 76% (valid), and science teachers obtained a score of 87,5% (valid), and student responses showed a positive valued with a score of 86%, in general students stated that the board game media was valid and easy to used. Furthermore, it could have been further developed towards the complexity aspect of the game on other science and biology topics that were more diverse and had their characteristics.